2005
DOI: 10.2174/1568010054022169
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial Cells and Glomerular Inflammation: From the Pathogenesis to Novel Therapeutic Approaches

Abstract: The mesangium occupies a central anatomical position in the glomerulus, and also plays an important regulatory role in immune-mediated glomerular diseases, with an active participation in the response to local inflammation. In general, the mesangial cell responses to the pathological stimuli are associated with the main events of glomerular injury: leukocyte infiltration, cell proliferation and fibrosis. Leukocyte migration and infiltration into the glomerulus is responsible for the initiation and amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 169 publications
(378 reference statements)
1
52
0
1
Order By: Relevance
“…The mesangium occupies a central anatomical position in the glomerulus, located between the fenestrated endothelial lining of the capillary lumen and the glomerular basement membrane. This structure is involved in the pathology of all types of chronic, progressive kidney diseases (26). The mesangium is composed of mesangial cells embedded in the mesangial matrix, providing structural support to capillary loops and modulating glomerular filtration (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesangium occupies a central anatomical position in the glomerulus, located between the fenestrated endothelial lining of the capillary lumen and the glomerular basement membrane. This structure is involved in the pathology of all types of chronic, progressive kidney diseases (26). The mesangium is composed of mesangial cells embedded in the mesangial matrix, providing structural support to capillary loops and modulating glomerular filtration (27).…”
Section: Discussionmentioning
confidence: 99%
“…The mesangium is composed of mesangial cells embedded in the mesangial matrix, providing structural support to capillary loops and modulating glomerular filtration (27). Mesangial cell responses to pathological stimuli are associated with the main events of glomerular injury, leukocyte infiltration, cell proliferation and NF-κB and MCP-1 expression (26,28). The present study demonstrated that the number of TUNEL-positive mesangial cells was significantly increased under high glucose conditions and CHOP was simultaneously induced.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular matrix accumulation in glomeruli contributes to the pathogenesis of glomerulosclerosis in fibrotic renal diseases (1)(2)(3)(4). Up-regulation of the renin-angiotensin system plays a key role in the initiation and the progression of glomerular injury via induction of extracellular matrix expansion in glomerular mesangial cells (MCs) 4 (4 -10).…”
mentioning
confidence: 99%
“…Cellular hypertrophy and extracellular matrix accumulation in glomeruli contributes to the pathogenesis of glomerulosclerosis in fibrotic renal diseases (1)(2)(3)(4)(5). The octapeptide hormone angiotensin II (Ang II) 2 is the dominant renin-angiotensin system effector (5)(6)(7) and is implicated in the pathogenesis of fibrosis of the glomerular microvascular bed.…”
mentioning
confidence: 99%